(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A simple eco-friendly green synthetic method was used to synthesize silver (Ag) nanoparticles as novel filtration beds. Materials and Methods: The Silver (Ag) nanoparticles were created by heating Azadirachtaindica (Neem) leaf extract to 70°C and reducing equimolar amounts of the salt mixture.There are two groups, each containing eight samples with G power 80% and coincidence interval of 95%.Results and Discussion: As a result, silver metallic nanoparticles were produced and analysed using UV–visible spectroscopy. UV–visible confirmed the evidence of silver nanoparticle formation. Using wastewater turbidity measurements, researchers looked at how dosage, pH, and agitation time affect turbidity reduction, P=0.04.Conclusion: Nanoparticles of silver (Ag) had higher maximum molecular suspension removal rates. In spite of the low molecular suspension concentrations, these nanoparticles work well as a novel filtration bed. In wastewater treatment, synthesized novel Ag nanoparticles can be used as efficient metal trace absorbers while also being environmentally acceptable (usingAzadirachtaindica).